Methodology for the optimization of resources, applied to virtual reality, through the use of WIFI network 6 - Auccahuasia, Wilver (2021)
Virtual reality is allowing to revolutionize many activities and allowing to achieve a realism very close to reality, one of the requirements to achieve these objectives is the use of computer resources for this work, such as memory, processor, storage capacity among others. The use of various devices where each one performs a specific task and then can be integrated, requires a connectivity structure that allows them to perform this work without problems at maximum speed and without loss of connectivity. This connectivity is achieved thanks to the use of the WIFI 6 protocol in its 5GHZ band, in this work a methodology is proposed that uses this connection in an educational application, where resources and information are shared between a computer and virtual reality glasses from the Oculus quest 2 brand, the results obtained are encouraging, having an ideal realism which is demonstrated by the child's concentration on the visualization of a high speed and maximum resolution video. The research concludes that the WIFI 6 protocol, in its 5GHZ working band, is the optimal one for virtual reality applications, managing to work with the security that connectivity is not lost and achieving an ideal realization by the shared use of the resources available in all the devices that make up the solution.